Design and manufacture of a self-balancing system for two-wheeled vehicle models using a reaction wheel - Indrawanto Indrawanto; Yuzar Arigi; Vani Virdyawan (International Journal of Electrical and Computer Engineering (IJECE), 2026)
Motorbikes are a popular mode of transportation in Indonesia and are agile in maneuvering on roads with heavy traffic. The increasing use of motorbikes has triggered many accidents. This paper discusses the design, manufacture, and control of a self-balancing system for a two-wheeled vehicle model to improve driving safety. The self-balancing system designed uses a reaction wheel. The system architecture consists of a microcontroller board, a DC motor, a gyroscope, a reaction wheel, and a two-wheel vehicle model. The dimensions of the reaction wheel are optimized between the mass and the moment of inertia to make it possible to self-balance the model from a certain initial angle. The controller is designed based on the state space model with a feedback linear-quadratic regulator controller. The matrix weighting values are selected using Bryson’s rules method. Experimental results show that the self-balancing system can work well for the two-wheel vehicle model.